Comparative Effectiveness of Darunavir 1,200 mg Daily and Approved Dosing Strategies for Protease Inhibitor-Experienced Patients - James M. Mikula; Chiu-Bin Hsiao; Joshua R. Sawyer; Qing Ma; Gene D. Morse (AIDS Research and Treatment)
Background. HIV protease inhibitors exhibit concentration-dependent viral inhibition. Higher once daily doses of darunavir boosted with ritonavir (DRV/r) may achieve viral suppression in place of twice daily dosing. International antiretroviral adherence guidelines recommend once daily regimens whenever possible. We present data on virologic suppression achieved with DRV 1,200 mg and ritonavir 100 mg once daily compared to approved DRV regimens. Methods. This retrospective observational study included all patients treated with DRV after documented use of another protease inhibitor at an urban immunodeficiency clinic. Data collection from inception of DRV use in August 2006 through March 2012 included patient demographics, viral loads, CD4+ cell counts, and resistance test results. The primary outcome of virologic suppression was defined as <50 copies/mL at 24 weeks. Differences in baseline characteristics and virologic outcomes across dosing groups were analyzed via one-way analysis of variance. Results. One hundred and thirty-five patients were included in the ITT analysis. Most patients had no known DRV RAMs at baseline. Virologic suppression rate was not different among treatment groups: 53.6% of patients on 1,200 mg daily, 52.3% on 600 mg twice daily, and 42.9% on 800 mg daily (P=0.568). Conclusions. Darunavir 1,200 mg daily should be investigated for use in protease inhibitor-experienced patients.